Recombinant adeno-associated virus carrying thymosin β 4 suppresses experimental colitis in mice - Zheng, Xiao-Yan; Lv, Yi-Fei; Li, Shuang; Li, Qian; Zhang, Qian-Nan; Zhang, Xue-Ting; Hao, Zhi-Ming (World journal of gastroenterology : WJG, 2017)
To investigate the protective effect of a recombinant adeno-associated virus carrying thymosin β (AAV-Tβ ) on murine colitis intracolonic administration. AAV-Tβ was prepared and intracolonically used to mediate the secretory expression of Tβ in mouse colons. Dextran sulfate sodium (DSS) was applied to induce the murine ulcerative colitis, and 2,4,6-trinitrobenzene sulfonic acid (TNBS) was used to establish a mouse colitis model resembling Crohn's disease. The disease severity and colon injuries were observed and graded to reveal the effects of AAV-Tβ on colitis. The activities of myeloperoxidase (MPO) and superoxide dismutase (SOD) and the content of malondialdehyde (MDA) were determined using biochemical assays. Colonic levels of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-10 were measured using ELISA, and mucosal epithelial cell apoptosis and proliferation were detected by TUNEL assay and immunochemistry, respectively. Recombinant AAVs efficiently delivered LacZ and Tβ into the colonic tissues of the mice, and AAV-Tβ led to a strong expression of Tβ in mouse colons. In both the DSS and TNBS colitis models, AAV-Tβ -treated mice displayed distinctly attenuated colon injuries and reduced apoptosis rate of colonic mucosal epithelia. AAV-Tβ significantly reduced inflammatory cell infiltrations and relieved oxidative stress in the inflamed colons of the mice, as evidenced by decreases in MPO activity and MDA content and increases in SOD activity. AAV-Tβ also modulated colonic TNF-α, IL-1β and IL-10 levels and suppressed the compensatory proliferation of colonic epithelial cells in DSS- and TNBS-treated mice. Tβ exerts a protective effect on murine colitis, indicating that AAV-Tβ could potentially be developed into a promising agent for the therapy of inflammatory bowel diseases.